A radical economic model of crime with an empirical test in non-city zip codes - Lynch, Michael J. (Critical criminology, 2016)
This article addresses three main issues. First, the structural explanation of crime rates across zip codes within a US county outside of that county’s major city’s limits. Second, this article addresses whether the traditional social disorganization argument which links measures of disorganized neighborhoods and in particularly deficiencies in informal social control to race, income inequality and poverty provides an adequate explanation of variations in non-city zip code crime rates. Third, this article also examines a radical critique of the kind of structural model posed by social disorganization, and tests an alternative radical economic model of crime at the zip code level. The empirical evidence illustrates the weakness of social disorganization explanations of crime at the zip code level. In contrast to those results, the empirical results for the proposed radical economic model of crime support its use for explaining crime across county zip codes. This type of empirical evidence demonstrates that radical models of crime have utility in explaining how economic structures influence the distribution of crime independently of variable identified in orthodox criminology.